Full‐Order Sliding‐Mode Control of Rigid Robotic Manipulators. Issue 3 (31st May 2018) - Feng, Yong; Zhou, Minghao; Yu, Xinghuo; Han, Fengling
Abstract: This paper proposes a full‐order sliding‐mode control for rigid robotic manipulators. The output signals of the proposed controller are continuous. Therefore, the controller can be directly applied in practice. A time‐varying gain is constructed to regulate the gain of the signum function in the sliding‐mode control so as to avoid the overestimation of the upper‐bounds of the uncertainties in the systems and reduce the waste of the control power. The chattering is attenuated by using a novel full‐order sliding manifold and establishing a novel ideal sliding motion. The proposed method is robust to the load disturbance and unmodeled parameters, especially to the unknown portion in the control matrix. Simulation results validate the proposed methods.